Case reportInsulinoma in a patient with long lasting type 2 diabetes - Araszkiewicz, Aleksandra; Zozulińska-Ziółkiewicz, Dorota; Wierusz-Wysocka, Bogna (Archives of Medical Science, 2009)
Insulinoma in a patient with pre-existing diabetes is rare. We describe a case of 68-year-old type 2 diabetic patient who after 20 years of disease experienced recurrent episodes of hypoglycaemia. Insulinoma was confirmed by elevated plasma insulin and C-peptide levels in fasting test and identification of pancreatic tumor in computer tomography. After surgical excision of the tumor, no further hypoglycaemic attacks occurred. However, the patient required insulin injections for satisfactory control of hyperglycaemia. In conclusion, insulinoma must be taken into consideration as a reason for hypoglycaemia in type 2 diabetes, however the coincidence of these two diseases is extremely rare.